A precise age for the Utopia Granite, southwestern New Brunswick, Canada - Barr, S.; Mortensen, J.; Bevier, M. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2010)
ABSTRACT The Utopia Granite is part of the Saint George Plutonic Suite, a gabbroic to granitic assemblage of plutons of Late Silurian – Late Devonian age in southwestern New Brunswick. New U-Pb (ID-TIMS) analyses of five fractions of strongly air-abraded zircon grains define a discordant array which suggests that all five fractions have suffered at least some minor degree of post-crystallization Pb-loss and yielded an imprecise upper intercept age of 426.3 ± 5.9 Ma. Fifteen zircon grains analyzed by LA-ICP-MS yielded overlapping concordant analyses, from which a weighted average of the 206Pb/238U ages, excluding one younger age, is 428.3 ± 1.0 Ma (MSWD = 0.66, probability of fit = 0.81), which we interpret as the best estimate for the crystallization age of the Utopia Granite. This age suggests that the Utopia Granite may be the oldest component of the Saint George batholith, and 5–8 million years older than plutons of the contiguous coastal Maine magmatic province to the southwest.